Syntheses and Biological Activity of Some Novel Mannich Bases - H. Havaldar, Freddy; Kumar J. Mishra, Sushil (Asian Journal of Chemistry, 2016)
3-Bromo-4-methoxybenzoyl hydrazine (1) was reacted with phenyl isothiocyanate to yield 1-(3'-bromo-4'-methoxybenzoyl)-4-phenylthiosemicarbazide (2) which on cyclization in alkaline medium afforded 3-(3'-bromo-4'-methoxyphenyl)-4-phenyl-1,2,4-triazolin-5-thione (3). The cyclized compound (3) on aminomethylation with formaldehyde and different amines furnished 3-(3'-bromo-4'-methoxyphenyl)-1-(substituted aminomethyl)-4-phenyl-1,2,4-triazolin-5-thiones (4a-e). The structures of the newly synthesized compounds have been established by analytical and spectral methods. These compounds have also been screened for their biological activity.